Work Engagement as the Mediator of the Relationship between Workplace Civility and Workplace Deviant Behaviour among Employees of Tertiary Institutions in Zamfara State (Lapai Journal of Economics, 2023)
This study explores the relationship between workplace civility, work engagement and workplace deviant behaviour, as well as the mediating role of work engagement in the relationship between workplace civility and workplace deviant behaviour. To this end, a survey was developed and administered to 424 employees across the selected tertiary institutions in Zamfara State, Nigeria. Structural equation modeling (SEM) was used to analyse the data collected. Results show that workplace civility has negative and significant effect on workplace deviant behaviour. Additionally, work engagement is also found to significantly mediate the relationship between workplace civility and workplace deviant behaviour. The study concluded that employers should promote a culture of workplace civility in order to maintain employee engagement and reduce workplace deviance. Furthermore, employers should also strive to foster an atmosphere of respect and appreciation among employees. The implications for further research on the topic are discussed.